The Relationship Between Parental Support, Peer Environment, and Coaching Parenting Patterns with The Motivation to Practice in Adolescent Soccer Athletes - David Cholik Perdana; Berliana; Mona Fiametta Febrianty (Universitas Negeri Semarang, 2025)
This study aims to determine how parental support, the peer environment, and the coach's parenting style relate to the motivation of adolescent soccer athletes to practice. This study is a quantitative descriptive study. The population used was 30 SSB BIONSA soccer athletes. The sampling technique in this study used the total sampling technique. The sample in this study was 30 SSB BIONSA soccer athletes. The instruments used were the Parental Support Questionnaire, Peer Support Questionnaire, Coach Parenting Style Questionnaire, and Training Motivation Questionnaire. Based on the results of the study, parental support has a significant relationship with a significant value of 0.04, the peer environment does not have a significant relationship with a significant value of 0.57, and coach parenting style has a significant relationship with a significant value of 0.00, so it can be concluded that parental support has a significant relationship with the motivation to practice of adolescent soccer athletes, the peer environment does not have a significant relationship with the motivation to practice of adolescent soccer athletes, and coach parenting style has a significant relationship with the motivation to practice of adolescent soccer athletes.